Divine motivation theory - Zagzebski, Linda Trinkaus, 1946- (Cambridge, UK ; New York : Cambridge University Press, 2004)
Widely regarded as one of the foremost figures in contemporary philosophy of religion, Linda Zagzebski has written a new book that will be seen as a major contribution to ethical theory and theological ethics. At the core of the book lies a new form of virtue theory based on the emotions. Quite distinct from deontological, consequentialist and teleological virtue theories, this one has a particular theological, indeed Christian, foundation. The new theory helps to resolve philosophical problems and puzzles of various kinds: the dispute between cognitivism and non-cognitivism in moral psychology, the claims and counterclaims of realism and anti-realism in the metaphysics of value, and paradoxes of perfect goodness in natural theology, including the problem of evil. As with Zagzebski's previous Cambridge book Virtues of the Mind, this new book will be sought out eagerly by a broad swathe of professionals and graduate students in philosophy and religious studies.
Includes bibliographical references (pages 389-404) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Christian ethics; Virtue; RELIGION -- Christian Theology -- Ethics; Christian ethics; Virtue; Meta-ethiek.; Deugden; Goddelijke deugden; Electronic books